Cover Image, Volume 33, Issue 6. (8th June 2022) - Chen, Keping; Liu, Xingbin; Hou, Xiaofeng; Qiu, Yuanhao; Lin, Jinxuan; Dai, Yan; Xu, Yuanning; Jiang, Lingyun; Zhou, Xiaohong; Zhang, Xue; Lu, Hongyang; Mara, Nicki; et al.
Abstract : The cover image is based on the Original Article Computed tomography imaging‐identified location and electrocardiographic characteristics of left bundle branch area pacing in bradycardia patients by Keping Chen et al., https://doi.org/10.1111/jce.15493 .